Réponses

  • Utilisateur Brainly
2014-03-22T11:54:35+01:00
F(A)           f(B)          f(A ∧ B)          f(A ∨ B)
----------------------------------------------------------------
0,25        0,32            0,17              0,40
0,10        0,55            0,08              0,57
0,35        0,36            0,35              0,36
0,12        0,53              0                0,67
---------------------------------------------------------------
Formule : f(A)+f(B)=f(A ∧ B)+f(A ∨ B)
merci beaucoup je vais en remettre 2 vois 3 d'exercice vous pourrez y regarder ?
merci beaucoup en tout cas